Reducing the energy demand of corn based fuel ethanol through salt extractive distillation enabled by electrodialysis - Hussain, Mohammed A.M.; Anthony, Jennifer L.; Pfromm, Peter H. (My University, 2011)
The thermal energy demand for producing fuel ethanol from the fermentation broth of a contemporary corn-to-fuel ethanol plant in the U.S. is largely satisfied by combustion of fossil fuels, which impacts the possible economical and environmental advantages of bio-ethanol over fossil fuels. To reduce the thermal energy demand for producing fuel ethanol, a process integrating salt extractive distillation – enabled by a new scheme of electrodialysis and spray drying for salt recovery – in the water-ethanol separation train of a contemporary corn-to-fuel ethanol plant is investigated. Process simulation using Aspen Plus® 2006.5, with the ENRTL-RK property method to model the vapor liquid equilibrium of the water-ethanol-salt system, was carried out. The integrated salt extractive distillation process may provide a thermal energy savings of about 30%, when compared with the contemporary process for separating fuel ethanol from the beer column distillate.
Keywords: Salt extractive distillation; Ethanol distillation; Fuel ethanol; Electrodialytic concentration; Bio-ethanol